Boardroom Behaviors of Outside Directors: The Effects of Trust and Distrust on CEO-Director Relations - YOSHIKAWA, Toru (Institutional Knowledge at Singapore Management University, 2009)
This paper presents a conceptual model that incorporates theoretical advancements in research in organizational behavior to examine CEO-director relations. We focus specifically on the effects of trust and distrust on the boardroom behaviors of corporate director; and how these behaviors affect the effectiveness of the director. We suggest that the levels of trust and distrust between a CEO and an individual director affect a director’s relative emphasis on monitoring or advisory roles.